Comparison of Cervical Vertebral Maturation with Fishman’s Skeletal Maturity Index Method in Assessment of Growth Status: Cervical Vertebral Maturation with Fishman’s Skeletal Maturity Index - ul Hassan, Faizan; Ayub, Ali; Hussain, Nadeem; Hussain, Sarfaraz; Khalid Memon, Madiha; Ali Rizvi, Ausaf; Ayman Bokhari, Saba; Mehmood Shah, Ahsan; Shams, Salman (Pakistan Journal of Health Sciences, 2022)
Assessment of skeletal maturity is paramount for orthodontists since optimal use and effectiveness of orthodontic and orthopedic appliances depends on it. Objective: To compare the cervical vertebral maturation (CVM) with Fishman’s hand wrist radiograph (HWR) method in assessment of growth status. Methods: This comparative cross sectional study was conducted at the Orthodontics department at the Khyber College of dentistry, Peshawar on 100 participants. The patients with 9 to 15 years of age, relatively well aligned arches, both genders, mild to moderate skeletal discrepancy, minimal dental compensations, vertical normal angle, and without temporomandibular joint disorders were included. Along with age and gender, stages of HWR and CVM were recorded. HWRs were acquired by standardized method and lateral cephalograms were taken in natural head position. The staging of HWR was done by using Fishman method while CVM staging. Comparison of CVM stages and Fishmann’s HWR stages were done using chi-square test. Results: The mean age was 11.79 ± 1.62 years. The females were 53(53%) and males were 47(47%). Most common stage of CVM was III (n=33, 33%) followed by IV (n=27, 27%). Similarly, common stage of hand wrist radiograph was III (n=32, 32%) followed by IV (n=28, 28%).There was no statistically significant different between two methods for assessing skeletal growth status (p=0.697). Conclusions: Cervical vertebral maturation can have used as an alternative to hand wrist radiograph for growth assessment without an extra radiation